Reducing stress during welfare inspection: validation of a non-intrusive version of the LayWel plumage scoring system for laying hens - Kjaer, J.B.; Glawatz, H.; Scholz, B.; Rettenbacher, S.; Tauson, R. (British poultry science, 2011)
1. The objectives of the present study were to validate a reduced, non-intrusive version (RLS) of the LayWel plumage scoring system in domestic laying hens with reference to complete, intrusive scoring (CLS) and to investigate the effect of these two scoring methods on corticosterone metabolite concentrations. 2. A total of 312 medium-heavy laying hens from 4 commercial hybrids kept in 24 floor pens were scored by two experienced teams. Another 150 hens from two hybrids kept in 6 pens were used for estimating scoring treatment effects on corticosterone metabolites in droppings. 3. Plumage scores were in general higher using the RLS method compared to the CLS method. The agreement between teams for plumage scores (CLS) were on a high (total score) to an excellent (single body part except breast and cloaca) level. 4. Birds subjected to CLS tended to have higher concentrations of corticosterone metabolites in droppings 2 h after scoring compared with birds in the control treatment (not scored). Birds subjected to RLS had intermediate concentrations. 5. It was concluded that a reduced version of the LayWel scoring system is a valid and reliable scoring method which tends to induce less stress to the subjects than the original procedure.